Membangun Negeri Dengan Wakaf Produktif - Selasi, Dini (Sharia Faculty Islamic Economic Law Study Department, 2021)
Waqf has a function of worship activities, namely by holding our assets to be used in the way of Allah SWT which gives rewards throughout the ages will also have a social function which after the principal of the property is withheld, developed then after being developed will provide results that can be used by the people. This research aims to provide education about the role of waqf in development as well as how the role of waqf for the welfare of the people. This research uses qualitative research methods, data collection techniques using secondary data and using literature study. The results of this study show that waqf has an important role in providing the welfare of the people and waqf also has an important role in developing the country, this is evidenced by the role of waqf in the fields of education, health, economy and finance, technology and agriculture, where these fields are the pillars of development national.